PSIKOEDUKASI KELUARGA UNTUK MENINGKATKAN KEMAMPUAN KELUARGA DALAM MERAWAT ANGGOTA KELUARGA DENGAN GANGGUAN JIWA - Florensa, Maria Veronika Ayu; Hasibuan, Shinta Yuliana; Bertylia, Bertylia (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
Background: Patients with mental disorders such as schizophrenia need family support in home care to reduce relapse and help patients return to productivity. Based on the results of a nursing assessment conducted to patients in the inpatient room of a special hospital in Western Indonesia, the causes of patient relapse include drug withdrawal and psychological stressors. The purpose of this community service is to provide psychoeducation for the patient's family to increase knowledge about how to care for patients with schizophrenia while at home so that they can be more productive and reduce relapse.Methods: This community service was carried out in the form of education and discussion in groups. Participants were families of patients admitted to one of the inpatient units of a regional special hospital with a medical diagnosis of schizophrenia and a problem of violent behavior. A pre and post-test was conducted to determine the level of family knowledge in caring for patients. Family psychoeducation was provided by a psychiatric nurse specialist in the patient's family group. Results: After being given family psychoeducation, it was found that there was an increase in the average family knowledge about how to care for patients with schizophrenia with risk problems for violent behavior. The majority of families said this activity was very useful because they could share experiences in caring for their sick family members, and provide mutual support between families.Recommendation: This activity is expected to form a family support group for patients with schizophrenia and become a medium for exchanging experiences and information about patient care.